Discounting and Digit Ratio: Low 2D:4D Predicts Patience for a Sample of Females - Aycinena, Diego; Rentschler, Lucas (Frontiers in Behavioral Neuroscience, 2018)
Inter-temporal trade-offs are ubiquitous in human decision making. We study the relationship between preferences over such trade-offs and the ratio of the second digit to that of the forth (2D:4D), a marker for pre-natal exposure to sex hormones. Specifically, we study whether 2D:4D affects discounting. Our sample consists of 419 female participants of a Guatemalan conditional cash transfer program who take part in an experiment. Their choices in the convex time budget (CBT) experimental task allow us to make inferences regarding their patience (discounting), while controlling for present-biasedness and preference for smoothing consumption (utility curvature). We find that women with lower digit ratios tend to be more patient.